Penerapan Teori Perkembangan Kognitif Jean Piaget dalam Pembelajaran Matematika di Sekolah - Sari, Mira Yulia; Suarni, Ni Ketut; Margunayasa, I Gede (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The aim of this research is to evaluate the impact of applying Jean Piaget's theory of cognitive development in the mathematics learning process in the school environment. This research uses an experimental design with a Nonequivalent Pretest Posttest Control Group Design pattern. The research subjects consisted of 5th grade students in elementary schools who were divided into two groups, namely the experimental group and the control group. Group selection was carried out using the cluster random sampling technique. Data from this research was collected using a test method using a test instrument for students' understanding abilities. Data were analyzed using the Polled Variance T test. The results of this research found that there was a significant influence on the application of Jean Piaget's theory of cognitive development in mathematics learning at school